Overview of Work Stress of Nurses Providing Services at Madani Regional Hospital Palu - Ladamu, Wawan; Harisa, Akbar (Indonesian Contemporary Nursing Journal (ICON Journal), 2025)
Aims: To determine the description of the work stress of nurses who provide services at Madani Regional Hospital Palu. Methods: This research is a quantitative research type with a descriptive design—sample selection using non-probability sampling type of purposive sampling as many as 149 nurses who provide nursing services. Data collection used the Indonesian version of the Expanded Nursing Stress Scale (ENSS) questionnaire, which has undergone validity and reliability tests. Results: The results of this study showed that the characteristics of the majority of nurse respondents were early adulthood aged 26-35 years (65.1%), work experience <5 years (53%), female gender ( 60.4 %), and married status (76.5%). Description of work stress of nurses with low work stress levels (56.4%) and high work stress (43.6%). Description of work stress of nurses based on characteristics of early adulthood low work stress (64.3%) high work stress (66.1%), work experience >5 years low work stress (42.9%) high work stress (52.3%), female gender low work stress (60.7%) high work stress (60%), married status low work stress (82.1%) high work stress (69.2%). Conclusion: This study's results show that most nurses experience low work stress, and almost half of nurses experience high work stress. High work stress is found at ages 26-35, with work experience >5 years, female gender, and married status. The factors causing high work stress were found in the subscale of problems with superiors and the subscale of workload.